Relation of Retail Gasoline and Diesel Prices in Croatia with Crude Oil Prices on World Markets - Karol Szomolańyi; Martin Lukaćik; Adriana Lukaćikova\' (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
According to many studies, the transmission of oil prices to retail fuel prices is asymmetric. Fuel prices react faster if oil prices rise and more slowly if oil prices fall. We use the simple and dynamic asymmetry models, error correction models, threshold autoregressive cointegration, and an approach based on the adjustment cost function in the linear-exponential form to verify the hypothesis of asymmetric reactions of gasoline and diesel prices in Croatia. The analysis uses a weekly time series of Croatian fuel prices obtained from the European Commission Weekly Oil Bulletin and BRENT oil prices from the US Energy Information Administration. Different standard econometric procedures lead to different results. Nevertheless, the approach based on the linear-exponential lost function confirmed the price asymmetries in the Croatian market.
Keywords: C26; C51; Q41; 330; asymmetry; retail gasoline prices; error correction model; threshold autoregressive cointegration; linear-exponential adjustment cost function; generalised method of moments; Croatia